Neuro4PD: An Initial Neurorobotics Model of Parkinson's Disease - Pimentel, Jhielson M.; Moioli, Renan C.; de Araujo, Mariana F. P.; Ranieri, Caetano M.; Romero, Roseli A. F.; Broz, Frank; Vargas, Patricia A. (Frontiers in Neurorobotics, 2021)
In this work, we present the first steps toward the creation of a new neurorobotics model of Parkinson's Disease (PD) that embeds, for the first time in a real robot, a well-established computational model of PD. PD mostly affects the modulation of movement in humans. The number of people suffering from this neurodegenerative disease is set to double in the next 15 years and there is still no cure. With the new model we were capable to further explore the dynamics of the disease using a humanoid robot. Results show that the embedded model under both conditions, healthy and parkinsonian, was capable of performing a simple behavioural task with different levels of motor disturbance. We believe that this neurorobotics model is a stepping stone to the development of more sophisticated models that could eventually test and inform new PD therapies and help to reduce and replace animals in research.